If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(3x + 6) + -6(7x + -3) = 0 Reorder the terms: 9(6 + 3x) + -6(7x + -3) = 0 (6 * 9 + 3x * 9) + -6(7x + -3) = 0 (54 + 27x) + -6(7x + -3) = 0 Reorder the terms: 54 + 27x + -6(-3 + 7x) = 0 54 + 27x + (-3 * -6 + 7x * -6) = 0 54 + 27x + (18 + -42x) = 0 Reorder the terms: 54 + 18 + 27x + -42x = 0 Combine like terms: 54 + 18 = 72 72 + 27x + -42x = 0 Combine like terms: 27x + -42x = -15x 72 + -15x = 0 Solving 72 + -15x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-72' to each side of the equation. 72 + -72 + -15x = 0 + -72 Combine like terms: 72 + -72 = 0 0 + -15x = 0 + -72 -15x = 0 + -72 Combine like terms: 0 + -72 = -72 -15x = -72 Divide each side by '-15'. x = 4.8 Simplifying x = 4.8
| 2x+9+2x+8+2x=2x+2x+3x+8 | | y=0.5x-0.2 | | 40v^2+19v-3=0 | | 4x+7y=-14 | | 4/x=8/40 | | 36-a=-36 | | a/8+7=8 | | 7a=10a/2 | | 10x+89=259 | | 1.33333x+2=0.25x+-9 | | 27=19w | | 2w+w=2(16/3) | | 6(x+1/8-2x-3/16)=3(3x/4-1/4)-3/8(3x-27) | | 32x+1918x-23=39(50x+71) | | h+2/5=7/15 | | (2/3)*3^2-5 | | X/2a=4a/x+2a | | 14+6n-8=18 | | 3r+13+r=41 | | -1-3t=-8t | | 8x+4x+4=40 | | 1.03x-4=-2.15+8.72 | | 2=6+a/2 | | 3x+6=2x+7-15x | | -5y-10=-16 | | 6-8x=7x-9x-30 | | -2(b+6)=-4 | | 3x+6=2x+6-15x | | 3x+6=2x+5-15x | | D+8/3 | | 3x+6=2x+4-15x | | 3x+6=2x+4-12x |